Palladium recovery from waste plating solutions using commercial resin lewatit TP 214 - Yegül, Ece Uluser (My University, 2021)
Bu çalışma, Lewatit TP 214 reçinesi üzerindeki Pd(II) metal iyonlarının adsorpsiyon davranışını incelemeyi amaçlamaktadır. Pd(II) metal iyonları, değerli metal kaplama solüsyonu atıklarından elde edilen amonyum içeren asidik solüsyon içinde çözündürüldü ve bu paladyum(II) klorür atık solüsyonu kaynak solüsyon olarak seçildi. Paladyum konsantrasyonu, bir atomik absorpsiyon spektrometresi kullanılarak 600 ppm olarak belirlendi ve deneysel çalışmalar için, başlangıç çözeltileri olarak pH 4 ve 7.5 olan 60 ppm Pd(II)'lik iki stok çözelti hazırlandı. Lewatit TP 214 (yoğunluk yaklaşık 1.1 g/ mL), bu çalışma için Pd(II) iyonları için seçici reçine olarak seçildi.Bu çalışma, dört parametreyi değiştirerek bir kesikli sistemde yapılmıştır; temas süresi, sıcaklık, Lewatit TP 214 miktarı ve çözelti pH'ı. Deneylerin başlangıcında sıcaklık deney serisine göre sırasıyla 25, 40, 50 ve 60ºC'de sabit tutulmuş ve her seferinde pH 4 veya 7.5'te iki ana stok çözeltiden biri kullanılmıştır. Stok çözeltilerdeki Lewatit TP 214 miktarı sırasıyla 100, 200, 300 ve 400 mg olarak belirlendi. Kör deneylerdeki performansından sonra ve deney çalışmalarının başında ilk çözümlere eklenmiştir. Her deney sırasında, kinetik çalışma için her 15 dakikada bir alikotlar alındı. Çalışmalar, pH'ı düşürerek, sıcaklığı artırarak ve adsorban miktarını artırarak geri kazanım yüzdesinin arttığını göstermiştir.

The aim of this study is to adsorb dissolved palladium (II) metal ions in the waste plating solution with Lewatit TP 214 commercial resin and to investigate the adsorption behavior of the resin. Pd(II) metal ions were dissolved in an acidic solution -containing ammonium- obtained from precious metal plating solution waste and, this palladium(II) chloride waste solution was selected as the source solution. The palladium concentration was determined as 600 ppm using an atomic absorption spectrometer, and for the experimental studies, two stock solutions of 60 ppm Pd(II) with a pH of 4 and 7.5 were prepared as initial solutions. Lewatit TP 214 (which has a density approximately 1.1 g/ mL) was chosen as the selective resin for Pd(II) ions for this study.The experiments were performed in a controlled batch system to examine four parameters; contact time, temperature, amount of Lewatit TP 214, and solution pH. At the start of the experiments, the temperature was kept constant at 25, 40, 50, and 60ºC based on the experiment series, respectively, and each time one of two main stock solutions at pH 4 or 7.5 was used. The amount of Lewatit TP 214 into the stock solutions was 100, 200, 300, and 400 mg, respectively. After its performance in the blank tests, these amounts were added into the initial solutions at the beginning of the experimental studies. During each experiment, aliquots were taken every 15 min for the kinetic study. The studies showed that the recovery performance was higher at lower pH, higher temperature, and higher amounts of the adsorbent.
Keywords: atık kaplama solüsyonu; Engineering; ion exchange resin; iyon değişim reçinesi; Lewatit TP 214; Lewatit TP 214 Palladium recovery; Metallurgy; Metalurji; Mühendislik; Paladyum geri kazanımı; waste plating solution